Bank Regulation and Supervision Ten Years after the Global Financial Crisis - Anginer, Deniz (World Bank, Washington, DC, 2019)
This paper summarizes the latest update of the World Bank Bank Regulation and Supervision Survey. The paper explores and summarizes the evolution in bank capital regulations, capitalization of banks, market discipline, and supervisory power since the global financial crisis. It shows that regulatory capital increased, but some elements of capital regulations became laxer. Market discipline may have deteriorated as the financial safety nets became more generous after the crisis. Bank supervision became stricter and more complex compared with the pre–global financial crisis period. However, supervisory capacity did not increase in proportion to the extent and complexity of new bank regulations. The paper documents the importance of defining bank regulatory capital narrowly, as the quality of capital matters in reducing bank risk. This is particularly true for large banks, because they have more discretion in the computation of risk weights and are better able to issue a variety of capital instruments.